Chronic renal impairment predicts oncological outcomes in UTUC patients undergoing RNU - Chris Ho-Ming Wong; Kang Liu; Hongda Zhao; Kubilay Sabuncu; Rahim Horuz; Selami Albayrak; Maria del Pilar; Laguna Pes; Jean de la Rosette; Jeremy Yuen-Chun Teoh (BMC Urology)
Abstract Objective This study aims to explore the relationship between pre-existing renal impairment and oncological outcomes in upper tract urothelial carcinoma (UTUC) patients treated with radical nephroureterectomy (RNU) using data from a multicentre international registry. Patients and methods Data on non-metastatic UTUC patients who underwent RNU were obtained from the Clinical Research Office of the Endourology Society Urothelial Carcinomas of the Upper Tract (CROES-UTUC) Registry. Patients were categorised into normal pre-operative renal function and chronic renal impairment (CKD) groups, with CKD defined as an estimated glomerular filtration rate below 60 mL/kg/1.73 m². Kaplan–Meier survival analysis was employed to investigate disease-free survival (DFS) and overall survival (OS). Multivariable Cox regression analysis was conducted to identify confounding variables. Results A total of 1393 patients diagnosed with UTUC who underwent RNU between 2014 and 2019 were analysed. 875 patients (62.4%) had normal renal function, whilst 528 patients (37.6%) had CKD prior to RNU. The two groups had similar proportions of bladder cancer history, comparable cardiovascular comorbidity, similar tumour stage, and comparable proportions receiving laparoscopic or robotic-assisted RNU. In multivariable cox regression analysis, CKD was found to be associated with inferior DFS (HR = 1.419; 95%CI = 1.060–1.898; p = 0.019). Upon multivariable analysis, pre-existing renal impairment and higher T stage (HR = 4.613; 95%CI = 1.829–4.712; p < 0.001) and the use of adjuvant chemotherapy (HR = 1.858; 95%CI = 1.229–2.807; p = 0.003) were also found to associate with worse DFS. Significant cardiovascular disease and higher T stage were associated with worse OS. Existing renal impairment at baseline did not have any significant associated with OS. Conclusion In this multicentre registry, preoperative chronic renal impairment was identified as an independent predictor of inferior DFS in patients undergoing RNU for non-metastatic UTUC. Preoperative CKD could serve as a clinical predictor of poorer oncological outcomes.